Zirconia stimulates ECM-remodeling as a prerequisite to pre-osteoblast adhesion/proliferation by possible interference with cellular anchorage - da Costa Fernandes, Celio J. [UNESP]; Ferreira, Marcel Rodrigues [UNESP]; Bezerra, Fábio J. B. [UNESP]; Zambuzzi, Willian F. [UNESP] (Springer Nature, 2018)
The biological response to zirconia (ZrO2) is not completely understood, which prompted us to address its effect on pre-osteoblastic cells in both direct and indirect manner. Our results showed that zirconia triggers important intracellular signaling mainly by governing survival signals which leads to cell adhesion and proliferation by modulating signaling cascade responsible for dynamic cytoskeleton rearrangement, as observed by fluorescence microscopy. The phosphorylations of Focal Adhesion Kinase (FAK) and Rac1 decreased in response to ZrO2 enriched medium. This corroborates the result of the crystal violet assay, which indicated a significant decrease of pre-osteoblast adhesion in responding to ZrO2 enriched medium. However, we credit this decrease on pre-osteoblast adhesion to the need to govern intracellular repertory of intracellular pathways involved with cell cycle progression, because we found a significant up-phosphorylation of Mitogen-Activated Protein Kinase (MAPK)-p38 and Cyclin-dependent kinase 2 (CDK2), while p15 (a cell cycle suppressor) decreased. Importantly, Protein phosphatase 2 A (PP2A) activity decreased, guaranteeing the significant up-phosphorylation of MAPK -p38 in response to ZrO2 enriched medium. Complementarily, there was a regulation of Matrix Metalloproteinases (MMPs) in response to Zirconia and this remodeling could affect cell phenotype by interfering on cell anchorage. Altogether, our results show a repertory of signaling molecules, which suggests that ECM remodel as a pre-requisite to pre-osteoblast phenotype by affecting their anchoring in responding to zirconia.